Выбор системной характеристики турбокомпрессорного агрегата на основе анализа его эффективности по результатам натурных испытаний. Ч. IV. Анализ системной характеристики турбокомпрессорного агрегата типа ГПА-Ц-6,3А и возможность оптимизации режимов его работы на стадии проектирования - Парафейник, В.П.; Тертышный, И.Н.; Прилипко, С.А.; Рябов, А.А. (Проблемы машиностроения, 2017)
С использованием функционального и функционально-эксергетического подходов, а также расчетных и экспериментальных данных об эффективности центробежного компрессора и газотурбинного двигателя получены системные характеристики агрегата ГПА-Ц-6,3А/56-1,45. Выполнена верификация расчетной модели для термодинамического анализа рабочего процесса блочно-комплектного турбокомпрессорного агрегата линейных компрессорных станций. З використанням функціонального і функціонально-ексергетичного підходів, розрахункових та експериментальних даних ефективності відцентрового компресора і газотурбінного двигуна отримані системні характеристики агрегату ГПА-Ц-6,3А/56-1,45. Виконана верифікація розрахункової моделі термодинамічного аналізу робочого процесу блочно-комплектного турбокомпресорного агрегату лінійних компресорних станцій. This paper presents the obtained system characteristics of the package GPA-C-6,3А /56-1,45 using functional and functional-exergy approaches as well as design and experimental data on efficiency of centrifugal compressor (CC) and gas turbine (GT). When functional approach served the package efficiency was 25,8%, and when functional-exergy approach served it was 26,5%. At this in both cases there is a difference between the optimum condition of the package operation at which the max efficiency of the package is reached, and design condition of centrifugal compressor operation. The specified differences are determined by using impellers with blades exit angle 320 and vaned diffusers in centrifugal compressor stages. The analytical dependence to determine TCA fuel efficiency factor is presented. Coincidence of optimum of characteristics of the package exergy efficiency and fuel consumption factor of centrifugal compressor weight output is determined. In this case the package max exergy efficiency meets min value of the fuel consumption value. Using experimental data the design model verification for thermodynamic analysis of the operating process of the skid turbo-compressor package of linear compressor stations having single casing centrifugal compressor is performed. It is shown that mismatching of max values of the package efficiency by weight output for TCA system characteristics is 2,0% (relative one), that provides the required accuracy of the parameters when TCA designing.